Current status of pesticide effects on environment, human health and it’s eco-friendly management as bioremediation: A comprehensive review - Pathak, Vinay Mohan; Verma, Vijay K.; Rawat, Balwant Singh; Kaur, Baljinder; Babu, Neelesh; Sharma, Akansha; Dewali, Seeta; Yadav, Monika; Kumari, Reshma; Singh, Sevaram; Mohapatra, Asutosh; Pandey, Varsha; et al. (Frontiers in Microbiology, 2022)
Pesticides are either natural or chemically synthesized compounds that are used to control a variety of pests. These chemical compounds are used in a variety of sectors like food, forestry, agriculture and aquaculture. Pesticides shows their toxicity into the living systems. The World Health Organization (WHO) categorises them based on their detrimental effects, emphasising the relevance of public health. The usage can be minimised to a least level by using them sparingly with a complete grasp of their categorization, which is beneficial to both human health and the environment. In this review, we have discussed pesticides with respect to their global scenarios, such as worldwide distribution and environmental impacts. Major literature focused on potential uses of pesticides, classification according to their properties and toxicity and their adverse effect on natural system (soil and aquatic), water, plants (growth, metabolism, genotypic and phenotypic changes and impact on plants defense system), human health (genetic alteration, cancer, allergies, and asthma), and preserve food products. We have also described eco-friendly management strategies for pesticides as a green solution, including bacterial degradation, myco-remediation, phytoremediation, and microalgae based bioremediation. The microbes, using catabolic enzymes for degradation of pesticides and clean-up from the environment. This review shows the importance of finding potent microbes, novel genes, and biotechnological applications for pesticide waste management to create a sustainable environment.